2005
DOI: 10.1902/jop.2005.76.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Surgical Infections: Prevalence Associated With Various Periodontal Surgical Procedures

Abstract: The results of this study confirm previous research demonstrating a low rate of postoperative infection following periodontal surgical procedures. Although perioperative antibiotics are commonly used when performing certain regenerative and implant surgical procedures, data from this and other studies suggest that there may be no benefit in using antibiotics for the sole purpose of preventing post-surgical infections. Further large-scale, controlled clinical studies are warranted to determine the role of perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
80
4
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 15 publications
6
80
4
5
Order By: Relevance
“…It is important to point out that although some authors have suggested that the adjunct use of antibiotics may reduce pain and swelling and improve healing, there is no sufficient evidence to support their use associated with periodontal surgery 32 . In an extensive review 33 of all the records available of periodontal surgeries in a sample of 395 patients and 1.053 periodontal surgery procedures, it was demonstrated that there were no benefits from antibiotics indication in these cases, due to the low rate of post-operative infections. Therefore, it is probable that the large number of indications found in the present study were made empirically.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that although some authors have suggested that the adjunct use of antibiotics may reduce pain and swelling and improve healing, there is no sufficient evidence to support their use associated with periodontal surgery 32 . In an extensive review 33 of all the records available of periodontal surgeries in a sample of 395 patients and 1.053 periodontal surgery procedures, it was demonstrated that there were no benefits from antibiotics indication in these cases, due to the low rate of post-operative infections. Therefore, it is probable that the large number of indications found in the present study were made empirically.…”
Section: Discussionmentioning
confidence: 99%
“…La cirugía periodontal causa una bacteriemia transitoria que se reduce de forma significativa con la utilización de profilaxis antibiótica (85). Aunque la utilización de antibioterapia en los procedimientos de cirugía periodontal es muy discutida, las infecciones postoperatorias se producen a pesar de que la prevalencia de éstas infecciones sea baja (86). Al retirar las suturas se produce también una bacteriemia transitoria (87).…”
Section: Analisis De La Patologia Periodontalunclassified
“…1,7,8 It may lead to postsurgical complications, such as excessive bleeding, infection, repositioning of the marginal gingiva, and inflammation. 7,9,10 Erbium lasers offer an alternative which is minimally invasive and eliminate most of the complications faced in a conventional procedure. 2 Healing time is also significantly reduced.…”
Section: Introductionmentioning
confidence: 99%